The role of epigenetics, bacterial and host factors in progression of Mycobacterium tuberculosis infection. (December 2018) - Marimani, Musa; Ahmad, Aijaz; Duse, Adriano
Abstract: Tuberculosis (TB) infection caused by Mycobacterium tuberculosis ( Mtb ) is still a persistent global health problem, particularly in developing countries. The World Health Organization (WHO) reported a mortality rate of about 1.8 million worldwide due to TB complications in 2015. The Bacillus Calmette-Guérin (BCG) vaccine was introduced in 1921 and is still widely used to prevent TB development. This vaccine offers up to 80% protection against various forms of TB; however its efficacy against lung infection varies among different geographical settings. Devastatingly, the development of various forms of drug-resistant TB strains has significantly impaired the discovery of effective and safe anti-bacterial agents. Consequently, this necessitated discovery of new drug targets and novel anti-TB therapeutics to counter infection caused by various Mtb strains. Importantly, various factors that contribute to TB development have been identified and include bacterial resuscitation factors, host factors, environmental factors and genetics. Furthermore, Mtb -induced epigenetic changes also play a crucial role in evading the host immune response and leads to bacterial persistence and dissemination. Recently, the application of GeneXpert MTB /RIF ® to rapidly diagnose and identify drug-resistant strains and discovery of different molecular markers that distinguish between latent and active TB infection has motivated and energised TB research. Therefore, this review article will briefly discuss the current TB state, highlight various mechanisms employed by Mtb to evade the host immune response as well as to discuss some modern molecular techniques that may potentially target and inhibit Mtb replication.